Isolation of microalgae with growth restriction and nutrient removal from alkaline wastewater - Fang, Ji; Yingkuan, Wang; Gang, Li; Yuguang, Zhou; Renjie, Dong (International Journal of Agricultural and Biological Engineering, 2015)
In order to isolate a well-tolerated microalgae strain and study its capability of wastewater treatment, a newly microalgae strain was isolated and identified from fresh water. The phylogenetic analysis indicates that this strain has a close relationship with Desmodesmus sp., named as EJ 9-2. The effects of temperature, pH value and NaCl concentration on growth of Desmondesmus sp. were investigated; the capability of nutrient removal from alkaline wastewater was also observed. Desmodesmus sp. EJ 9-2 had a wide pH adaptation range (3-12) and could remove nitrogen, phosphorus and COD which might substantially decrease the cost of biofuel production. The research can provide evidence for outdoor large-scale cultivation of microalgae.Keywords: microalgae, isolation, growth restriction, alkaline wastewater, nutrient removal, algae-based fuel, wastewater treatmentDOI: 10.3965/j.ijabe.20150806.2164Citation: Ji F, Wang Y K, Li G, Zhou Y G, Dong R J. Isolation of microalgae with growth restriction and nutrient removal from alkaline wastewater. Int J Agric & Biol Eng, 2015; 8(6): 62－68.